Available versus used prey – Combined methods reveal the breeding diet of the European roller (Coracias garrulus) in Serbia - Milinski, Lea; Arok, Maja; Matić, Ivana; Nikolić, Tijana; Radišić, Dimitrije (Biologia Serbica, 2022)
The European roller (Coracias garrulus) is a threatened species, and over the last few decades population recovery has been achieved via installation of nest boxes as a substitute for lost natural nesting sites. However, lack of available food acts as a second limiting factor for the roller. Thus, in the present study, the dietary requirements of rollers were investigated to provide necessary data to guide conservation measures that encourage the return of rollers to their breeding sites. Field work was carried out within roller breeding territories in the Central Banat region (Serbia). Prey availability and preferences were determined by comparing available and consumed prey over five breeding seasons. Different proportions of main prey categories within the roller’s diet were detected, comparing available prey and consumed prey, which led to negative Ivlev index values. Consumed prey remains found in nest boxes constituted larger amounts of coleopterans, while orthopterans were more numerous in the available prey. This finding is not surprising as orthopterans, unlike coleopterans, are soft-bodied and swallowed as whole specimens leaving less detectable body parts among food remains, which could lead to their underestimation in the roller diet. Apiaries were found near the research plots, resulting in a higher proportion of hymenopterans among the available invertebrate prey. In contrast, we only found one bee specimen in the nest box. This confirms that rollers avoid hunting fast flying insects. The low percentage of orthopterans within the pitfall traps has been complemented by sweep net catches. Therefore, this combination of methods resulted in a composition of available prey that corresponds to the observed food remains. A variety of prey groups were found to be part of the roller diet composition. Most of these were arthropods, while 5% of vertebrates were detected (amphibians, reptiles and small mammals). Because of this, we propose that the European roller is an opportunistic predator that can survive near poor, overgrazed, and dry pastures.